Analyzing the dietary intake of junior tennis players - Young Kim, B.; Reznik Dolins, K. (Medicine and Science in Tennis, 2009)
The impact of nutritional counseling on the dietary intake of junior tennis players was investigated in two groups of athletes aged 10-17 years using 3-day dietary records and a questionnaire. Both groups consisted of highly trained, competitive players; only one group of subjects received nutritional counseling (Altheus group) while the other group did not (USTA group). There were no significant differences in age or body mass index between the groups. The Altheus group met all recommendations except for fluid intake while their counterparts in the USTA group fell shorts of recommendations for calories, carbohydrates, fluids, and calcium. These results indicate the benefits of nutritional counseling and the need for greater emphasis on nutritional education for our nation`s young athletes.